Injuries and Deaths That Resulting From Bicycle and Motorcycle Accidents - Sataloğlu, Neva Danışkan; Aydın, Berna; Turla, Ahmet (The Bulletin of Legal Medicine, 2010)
In this study, it is aimed at illuminating how the the injuries resulted from accidents occurred, suggesting solutions for less serious injuries namely in traffic accidents, by studying the de-mographical and clinical characteristics of cases injured or died as the result of bicycle and motorcycle accidents. 256 cases, injured in bicycle and motorcycle accidents and received medical attention and treatment in Ondokuz Mayis University (OMU) Faculty of Medicine are studied, demographic and clinical datas of these cases are evaluated with SPSS 10.0 package programme. Those injured both by bicycle and motorcycle accidents were mostly male (89.1%). Bicycle accidents were mostly seen in 10-19 age group and motorcycle accidents were mostly seen in 20-29 age group. It is confirmed that bicycle accidents resulted mostly from falling, and motorcycle accidents from crash, that in both groups facial region was commonly injured, and this was followed by upper extremity in bicycle accidents and head in motorcycle accidents. All data show that motorcycle and bicycle use has been increasing rapidly in our country and all over the world. In parallel to this, accidents resulting from these vehicles are also increasing in number. Serious precautions must be taken immediately to prevent this problem from reaching to serious dimensions.Key words: Traffic accident, bicycle, motocycle, injury, death.
Keywords: traffic accident; bicycle; motocycle; injury; death